Modulation of the functional association between the HIV-1 intasome and the nucleosome by histone amino-terminal tails - Benleulmi, Mohamed S. (Retrovirology, 2017)
BACKGROUND: Stable insertion of the retroviral DNA genome into host chromatin requires the functional association between the intasome (integrase·viral DNA complex) and the nucleosome. The data from the literature suggest that direct protein–protein contacts between integrase and histones may be involved in anchoring the intasome to the nucleosome. Since histone tails are candidates for interactions with the incoming intasomes we have investigated whether they could participate in modulating the nucleosomal integration process. RESULTS: We show here that histone tails are required for an optimal association between HIV-1 integrase (IN) and the nucleosome for efficient integration. We also demonstrate direct interactions between IN and the amino-terminal tail of human histone H4 in vitro. Structure/function studies enabled us to identify amino acids in the carboxy-terminal domain of IN that are important for this interaction. Analysis of the nucleosome-binding properties of catalytically active mutated INs confirmed that their ability to engage the nucleosome for integration in vitro was affected. Pseudovirus particles bearing mutations that affect the IN/H4 association also showed impaired replication capacity due to altered integration and re-targeting of their insertion sites toward dynamic regions of the chromatin with lower nucleosome occupancy. CONCLUSIONS: Collectively, our data support a functional association between HIV-1 IN and histone tails that promotes anchoring of the intasome to nucleosomes and optimal integration into chromatin. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12977-017-0378-x) contains supplementary material, which is available to authorized users.